2019
DOI: 10.1186/s12913-019-4721-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to recruitment and enrollment of HIV-infected individuals with opioid use disorder in a clinical trial

Abstract: BackgroundThe CTN-0067 CHOICES trial tests implementation of extended-release naltrexone (XR-NTX) versus treatment-as-usual (TAU) for opioid use disorders (OUD) in HIV clinics to improve HIV viral suppression. The study team investigated recruitment strategies to elucidate the barriers and facilitators to recruitment and enrollment in the study.Main textMethods: Semi-structured, in-depth, digitally recorded interviews were completed with study recruitment-related staff and medical providers (n = 26) from six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…For potential participants, having a lack of trust in research, doctors, investigators, drugs, and the medical industry was a recurring theme across the literature [ 14 – 16 , 19 , 20 , 22 24 ]. This may arise from previous bad experiences and previous severe adverse events in reported studies [ 25 ] and was often compounded by related beliefs or fears [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…For potential participants, having a lack of trust in research, doctors, investigators, drugs, and the medical industry was a recurring theme across the literature [ 14 – 16 , 19 , 20 , 22 24 ]. This may arise from previous bad experiences and previous severe adverse events in reported studies [ 25 ] and was often compounded by related beliefs or fears [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results are also consistent with another recent investigation which found that it is more difficult to induct patients onto XR-NTX than buprenorphine, though requirements for a negative-buprenorphine urine sample before XR-NTX induction may have exacerbated the underlying withdrawal tolerance issues [ 19 ]. Additionally, in a previous study of CHOICES study staff, Hoffman et al [ 21 ] found that a specific medication-related barrier to induction was patient fear of opioid abstinence required prior to XR-NTX induction. Similar results have been found in other studies of individuals using stimulants and opioids [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While long-acting formulations may improve treatment adherence, a recent study found that it was more difficult to initiate XR-NTX than buprenorphine in patients with OUD [ 19 ]; the process of initiating XR-NTX so that someone receives their first injection (a.k.a. “induction”) requires an opioid-free state several days prior to initiation, and opioid withdrawal can be difficult to complete even in inpatient settings with supportive medication [ 21 ]. In contrast, buprenorphine induction does not require complete abstinence from opioids; first dose of buprenorphine may be administered 12–24 h after last use of opioids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PLWHA with substance use disorders face additional challenges due to unique economic and racial/ethnic disparities. Recent works identified poverty as a risk factor for lower rates of linkage to care [ 26 ] and enrollment in supportive services within this unique population [ 27 ]. There were also several studies that evaluated racial and ethnic differences among PLWHA with substance use disorders.…”
Section: Disparities In Healthcare and Access To Care In Plwhamentioning
confidence: 99%